Beyond the discourse of globalization (Glocalism: Journal of Culture, Politics and Innovation, 2015)
This paper deals with the ways in which discourse concerning planet earth is being transcended. Specifically, attention is drawn to the increasingly overlapping relationship between the work of philosophers and anthropologists, one the one hand, and astrophysicists on the other. Woven into the discussion are the issues of the neglect of global consciousness and culture in comparison with the more usual concern with global connectivity. In this respect it is argued that globalization, as it is normally understood, can be regarded as self-destroying when it is considered under the rubric of glocalization. The paper concludes with discussion of the possibility of some form of global governance in the light of the present chaotic state of global affairs. It is argued that some relatively clear-cut image of the world as a whole is a precondition of any systematic attempt to resolve this problem. The attempt to provide such an image rests upon the author’s previous discussions of the global field.
Keywords: global consciousness; glocalization; governance; global problems; cosmos